The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00014086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eel (Anguilla anguilla L.) removals from selected sites of a stream on its subsequent densities

Abstract: We assessed the effect of eel (Anguilla anguilla) removal from three sites of a Cantabrian stream upon its subsequent densities. In the first sample (Sept. 1986) numbers and densities were estimated as 43, 45 and 84 ind and 3490,3030 and 3750 ind ha-'. Removal of these eels reduced the subsequent numbers and densities which, except on two occasions, were never reached again during the two years (eleven estimates) of study. Highest densities were recorded in the uppermost site in May and July, 1987, coincident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The strong site fidelity and the alternative use of a precise residence site observed imply the existence of a mechanism by which this fidelity is acquired, as well as the development of precise sensory recognition of the site involved (Braithwhaite and De Perera 2006). It helps to understand why eels tend to home to their capture site after a forced translocation (Rossi et al 1987; Lobon-Cervial et al 1990;McCleave and Arnold 1999). Interestingly, in the context of the hydroelectric production in the Mehaigne, a greater preference for the natural flow regime over the minimum flow zone could be related to extremely less available cryptic habitats in the latter zone due to their emergence because of a lower water level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong site fidelity and the alternative use of a precise residence site observed imply the existence of a mechanism by which this fidelity is acquired, as well as the development of precise sensory recognition of the site involved (Braithwhaite and De Perera 2006). It helps to understand why eels tend to home to their capture site after a forced translocation (Rossi et al 1987; Lobon-Cervial et al 1990;McCleave and Arnold 1999). Interestingly, in the context of the hydroelectric production in the Mehaigne, a greater preference for the natural flow regime over the minimum flow zone could be related to extremely less available cryptic habitats in the latter zone due to their emergence because of a lower water level.…”
Section: Discussionmentioning
confidence: 99%
“…During the growth phase (yellow eel), they must have access to suitable habitats and substantial food resources for an accumulation of energy reserves useful to complete the eel's reproductive cycle to the Sargasso Sea (Maes et al 2005;Belpaire et al 2009). Lobon-Cervial et al (1990) and Laffaille et al (2003) have observed sedentary behavior of large yellow eels in rivers. During the freshwater phase, eels colonize a wide repertoire of habitats depending on sites and rivers (Baras et al 1998;Laffaille et al 2003), in which flow regime synchronized with temperature and day length play a profound role in fish live (Bunn and Arthington 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown in freshwater marshes (Baisez 2001), in river systems of Europe (Feunteun et al., unpublished data) and in estuaries (Secor & Morrison 2001). Thirdly, Lobon‐Cervia et al. (1990) have shown that, when density is depleted by fisheries, extremely slow recovery of the population is observed, suggesting that eels from neighbouring areas stay within their home range, regardless of available habitats.…”
Section: Discussionmentioning
confidence: 99%
“…eels exploiting more efficiently an environment which they have already experienced. The attachment to precise loci may proportionally be higher in densely populated environments, such as the Awirs stream, where the population density is sensibly higher than in most European waters (Tesch, 1977;Lobon-Cervia et al, 1990;Barak & Mason, 1992).…”
Section: Discussionmentioning
confidence: 99%